Characterization, molecular cloning and localization of calreticulin in Eisenia fetida earthworms - Silerová, Marcela; Kauschke, Ellen; Procházková, Petra; Josková, Radka; Tucková, Ludmila; Bilej, Martin (Gene, 2007)
Calreticulin is a highly conserved calcium-binding protein affecting many cellular processes inside and outside of the endoplasmic reticulum (ER). It participates in the regulation of Ca(2+) homeostasis, acts as a chaperone and modulates gene transcription, integrin-mediated cell signalling as well as cell adhesion. Here we report on the sequence characterization of a calreticulin-coding cDNA of Eisenia fetida earthworms. The neighbor-joining phylogeny tree constructed based on the deduced amino acid sequence indicates a common origin of the E. fetida calreticulin molecule and that of mollusks. A polyclonal anti-calreticulin antibody used for immunocytochemistry and immunohistochemistry localized the protein in the mesenchymal lining of the coelomic cavity and in coelomocytes of E. fetida. In situ hybridization revealed high expression of E. fetida calreticulin in various cells and tissues, namely epidermis, neurons of the ventral nerve cord, intestine, sperms, body wall muscles and some coelomocytes. Real-time PCR confirmed the strong expression of calreticulin in the nervous system, particularly in cerebral ganglia, in body wall muscles and in seminal vesicles. Moreover, a high calreticulin expression was measured in the muscular pharynx.
Keywords: Molecular Sequence Data; Tissue Distribution; sekvence aminokyselin; DNA, Complementary; imunohistochemie; rekombinantní proteiny; mužské pohlaví; Recombinant Proteins; Cloning, Molecular; Base Sequence; sekvence nukleotidů; Immunohistochemistry; Oligochaeta; ženské pohlaví; komplementární DNA; zvířata; tkáňová distribuce; Amino Acid Sequence; fylogeneze; Calreticulin; hybridizace in situ; klonování DNA; kalretikulin; molekulární sekvence - údaje; Female; Phylogeny; In Situ Hybridization; Male; Animals